COMPARATIVE ANALYSIS OF ISLAMIC AND WESTERN APPROACHES TOWARD ANIMAL WELFARERIGHTS - Dr. Omar Abdallah Dukuly; Dr. Usman Jimoh Muhammad (BNBWU Journal of Multidisciplinary Research, 2025)
A search is made into Comparative Analysis of Islamic and Western Approaches toward Animal Welfarerights. Globally, people treat animals with contempts and thereby abuse their rights. Scruton (2000) argues that animals can not enter into any collective contract or make ethical choices, and therefore cannot be regarded as owners of rights.The view of animals’ insensibility to pain, accounts for ram fights, bullfights, whipping horses and donkeys to death as they resist along with heavy loads of stone, sand, firewood etc...It has called for the attentions of concerned individuals and groups of individuals in the western wolrd since 19th century to address the problems of animal abuse. Their approach and that of Islam, which has been in place since 7th century A.C, are studied in this research. It was discovered that there are certain extreme ideas in the western approach. For example, some animal right activists believe that animals should not be killed for food. It was recommended to appreciate Islamic position which of course advocates animal rights and at the same time allows decent use of animals for food, transportation etc.